PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MELALUI MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) KELAS VIII - Wahyu Alhadiyansyah; Jumroh Jumroh; Anggria Septiani Mulbasari (Jurnal Math-UMB.EDU, 2019)
This study aims to determine whether there is no increase in problem solving skills through the Creative Problem Solving (CPS) learning model for Grade VIII students of SMP Negeri 7 Palembang. This experimental research uses One Groups Pretest-Posttest Design, with a population of 324 students of Palembang 7 Junior High School students and a sample of 27 students taken by cluster sampling technique, which is an experimental class that is treated with Creative Problem Solving (CPS) learning model. The variables measured in this study were improvement in problem solving ability and treatment variables, namely Creative Problem Solving Learning Model (CPS). The subjects in this study were class Â and used descriptive research methods. Data collection techniques using the test. The analysis technique used in this study is the N-Gain Test. Based on the results of the analysis of the N-Gain test data the initial test (pretest) and the final test (posttest) obtained a gain index of 0.62 with moderate interpretation with an average pretest value of 30.9 and an average posttest value of 72.6. These results indicate that there is an increase in problem solving skills through the Creative Problem Solving (CPS) learning model for VIII grade students of SMP Negeri 7 Palembang.Keywords: Problem Solving Ability, Creative Problem Solving (CPS) Learning Model.